Correlation of Physical Activity with Fear of Fall in Patients with Total Knee Replacement - A Research Protocol - Nupur Thombare1 Shalaka Dhankar2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: An elderly patient who has undergone total knee replacement may have fear of fall. Fear offall after TKR and its impact on physical activity is sparsely researched. This study was aimed to find acorrelation of physical activity with fear of fall in patients with Total Knee Replacement. Physical activity isassessed using the Physical activity scale for the elderly (PASE) Scale. The PASE Scale is understandable,reliable, and is a valid tool to assess physical activity in the elderly. Fall efficacy scale (FES) is a valid toolto assess fear of fall. Objectives: The objective of the current study is to assess physical activity and fearof fall and to find Correlation of physical activity with fear of fall in patients with TKR. Methods: Thisstudy will be carried out in Physiotherapy OPD, Ravi Nair Physiotherapy College and AVBRH HospitalSawangi Meghe, Wardha .100 Patients undergone TKR will be examined. Physical activity and fear of fallwill be assessed using the PASE scale and Fall Efficacy Scale respectively. Results: Upon completion ofthe Study result will be estimated by statistical analysis. Conclusion: After going through various studies,maximum studies indicated that there is a decrease in physical activity in patients with TKR but very fewstudies indicated fear of fall in the patients. Therefore, the current study is being carried out which couldhelp to reach the conclusion to find whether there is any correlation between physical activity and fear offall in patients undergone TKR. Because rehabilitation after TKR is mainly concentrated on improving thephysical function however if the patient has fear of fall this may interfere with the patient returning to his orher physical activity